Usnea improves high-fat diet- and vitamin D3-induced atherosclerosis in rats by remodeling intestinal flora homeostasis - Liu, Yanjun; Dou, Chongyang; Wei, Guihua; Zhang, Liudai; Xiong, Wei; Wen, Lingmiao; Xiang, Chunxiao; Chen, Chunlan; Zhang, Tinglan; Altamirano, Alvin; Chen, Yunhui; Zhang, Tian-e; et al. (Frontiers in Pharmacology, 2022)
Background: Usnea has various pharmacological properties, including anti-inflammatory, antitumor, antioxidant, antiviral, and cardiovasculoprotective effects. Aim of the study: To investigate the potential mechanisms underlying the anti-atherosclerosis (AS) activity of Usnea ethanol extract (UEE) via the regulation of intestinal flora. Materials and Methods: The chemical composition of UEE was determined using ultra-performance liquid chromatography with quadrupole exactive orbitrap mass spectrometry (UPLC-Q-EOMS). Thirty-six male Sprague–Dawley rats were divided into six groups. A high-fat diet and intraperitoneal vitamin D3 injections were used to establish a rat model of AS. After 4 weeks of treatment with UEE, hematoxylin–eosin staining was performed to evaluate the pathomorphology of the aorta, liver, and colon. The composition and diversity of the rat intestinal flora were determined using high-throughput 16S rRNA sequencing. Enzyme-linked immunosorbent assays were used to measure the levels of plasma trimethylamine oxide (TMAO), serum bile acid (BA), total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), lipopolysaccharide (LPS), tumor necrosis factor-alpha (TNF-α), and interleukin-6 (IL-6). The protein expression of cholesterol 7α-hydroxylase (CYP7A1) and flavin monooxygenase 3 (FMO3) in the liver and zonula occludens-1 (ZO-1) and occludin in colon tissue was detected via western blotting. Results: Forty-four compounds were identified in UEE. In the rat model of AS, UEE significantly prevented calcium deposition; decreased the serum levels of TC, TG, LDL-C, LPS, TNF-α, and IL-6; and increased the serum level of HDL-C. Additionally, all UEE dosages decreased the relative abundance of Verrucomicrobiota while increased that of Bacteroidetes. FMO3 protein expression and TMAO levels decreased, whereas CYP7A1 protein expression and BA levels increased. The absorption of intestinal-derived LPS was minimized. Furthermore, the protein expression of ZO-1 and occludin was upregulated. Conclusion: UEE ameliorated AS. The underlying mechanism was the reversal of imbalances in the intestinal flora by Usnea, thereby inhibiting calcium deposition, abnormal lipid metabolism, and inflammatory response.